Christianity and National Identity in Twentieth-Century Europe Conflict, Community, and the Social Order - Wood, John Carter (Veröffentlichungen des Instituts für Europäische Geschichte Mainz, 2016)
This collection explores how Christian individuals and institutions combined the topics of faith and national identity in twentieth-century Europe. "National identity" is understood in a broad sense that includes discourses of citizenship, narratives of cultural or linguistic belonging, or "national" characteristics. It considers various geographical contexts, and takes into account processes of cross-national exchange and transfer. It shows how national and denominational identities were often mutually constitutive, at times leading to a strongly exclusionary stance against "other" national or religious groups. In different circumstances, religiously minded thinkers critiqued nationalism, emphasising the universalist strains of their faith, with varying degrees of success. Throughout the century church officials and lay Christians have had to come to terms with the relationship between their national and "European" identities within the processes of Europeanisation.